New insights into the sensitization to nonspecific lipid transfer proteins from pollen and food: New role of allergen Ole e 7. Issue 4 (6th November 2019) - Oeo‐Santos, Carmen; Navas, Ana; Benedé, Sara; Ruíz‐León, Berta; Díaz‐Perales, Araceli; Vogel, Lothar; Moreno‐Aguilar, Carmen; Jurado, Aurora; Villalba, Mayte; Barderas, Rodrigo
Abstract: Background: Ole e 7 is a nonspecific lipid transfer protein (nsLTP) from olive pollen, one of the main allergenic pollens worldwide. This allergenic nsLTP is responsible for severe symptoms in regions with high olive pollen exposure, where many Ole e 7‐sensitized patients exhibit a co‐sensitization to the peach nsLTP, Pru p 3. However, there is no evidence of cross‐reactivity, which explains this observed co‐sensitization. Therefore, the purpose of this study was to explore the relationship between Ole e 7 and Pru p 3. Methods: A total of 48 patients sensitized to Ole e 7 and/or Pru p 3 were included in the study. Specific IgE serum levels were measured by ImmunoCAP 250 and ELISA. Inhibition assays were performed to determine the existence of cross‐reactivity between both nsLTPs. Allergic response was analyzed ex vivo (basophil activation test) and in vitro (RBL‐2H3 mast cell model). Results: Common IgG and IgE epitopes were identified between both allergens. IgE‐binding inhibition was detected in Ole e 7–monosensitized patients using rPru p 3 as inhibitor, reaching inhibition values of 25 and 100%. Ex vivo and in vitro assays revealed a response against rPru p 3 in four (31%) Ole e 7–monosensitized patients. Conclusions: Our results suggest that Ole e 7 could play a new role as primary sensitizer in regions with high olive pollen exposure, leading to the peach nsLTP sensitization. This co‐sensitization process would occur because of the cross‐reactivity between Ole e 7 and Pru p 3 observed in some allergic patients. Abstract : Ole e 7 cross‐reacts with nonspecific lipid transfer proteins (LTPs) from pollen and food, specifically with peach and pear. Common IgG and IgE epitopes were identified between Ole e 7 and Pru p 3 despite their low amino acid sequence identity. Ole e 7 could act as primary sensitizer in regions with high olive pollen exposure, leading to Pru p 3 sensitization.